Prediction of voltage over electrodes' filaments of fluorescent lamps during dimming operation - Wakabayashi, Fabio Toshiaki [UNESP]; Canesin, Carlos Alberto [UNESP]; Dantas, Fausto Donizeti; Pinto, João Onofre Pereira (Institute of Electrical and Electronics Engineers (IEEE), 2005)
This paper presents an investigation concerning the use of fundamental approximation analysis and a new lamp model for the prediction of the voltage over electrodes' filaments during dimming operation. The lamp model employed in this paper is based on equivalent resistances, which represent the electrodes' filaments and the gas column of a F32T8 lamp. Experimental results are presented in this paper, indicating the validity of the proposed analysis and confirming its potential to serve as an effective tool for the design of dimming electronic ballasts. © 2005 IEEE.
Keywords: Dimming operation; Electronic ballasts; Lamp model; Ballasts (lamp); Electric potential; Electric resistance; Electrodes; Fluorescent lamps